Stakeholder capitalism : a global economy that works for progress, people and planet - Schwab, Klaus, 1938- (John Wiley & Sons, Inc., 2021)
"Professor Klaus Schwab is Founder and Executive Chairman of the World Economic Forum, the International Organization for Public-Private Cooperation. He is one of the most recognizable thought leaders in economics in the world, with the Forum as his platform. The Forum is simple and effective: it brings together the most relevant leaders from all sectors of global society and identifies the best ways to address the world's most significant challenges. It works. For almost 50 years, the Forum has been the catalyst for global initiatives, historic shifts, industry breakthroughs, economic ideas and tens of thousands of projects and collaborations. The Forum is best known for its Annual Meeting in Davos-Klosters. Through the years, numerous business, government and civil society leaders have made their way to the high Alps to consider the major global issues of the day and to brainstorm on solutions to address these challenges."--